2015
DOI: 10.1890/14-1510.1
|View full text |Cite
|
Sign up to set email alerts
|

Rapoport's Rule: Do climatic variability gradients shape range extent?

Abstract: The trend of increasing latitudinal range sizes of species towards higher latitudes, known as Rapoport's Rule, has been highly controversial in the literature since it was first proposed by Stevens in 1989. We contend that the question of interest is not whether general global patterns occur, nor whether they support or refute Rapoport's Rule, but whether the mechanism thought to underlie such patterns, the Climatic Variability Hypothesis, is supported. The Climatic Variability Hypothesis suggests that taxa or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 77 publications
4
88
0
Order By: Relevance
“…For example, it is possible that the model of Stevens ' (1989) works only when larger range sizes would covary with reduced range overlap, and Šizling et al (2009) indeed showed that Rapoport's pattern will not generate the LDG if this assumption is not met. Support for the generality of Rapoport's rule has been quite variable (Gaston et al, 1998;Pintor et al, 2015;Tomašových et al, 2016): both findings for (Rohde et al, 1993) and against (Rohde, 1992) the existence of the rule have emerged. Support for the generality of Rapoport's rule has been quite variable (Gaston et al, 1998;Pintor et al, 2015;Tomašových et al, 2016): both findings for (Rohde et al, 1993) and against (Rohde, 1992) the existence of the rule have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is possible that the model of Stevens ' (1989) works only when larger range sizes would covary with reduced range overlap, and Šizling et al (2009) indeed showed that Rapoport's pattern will not generate the LDG if this assumption is not met. Support for the generality of Rapoport's rule has been quite variable (Gaston et al, 1998;Pintor et al, 2015;Tomašových et al, 2016): both findings for (Rohde et al, 1993) and against (Rohde, 1992) the existence of the rule have emerged. Support for the generality of Rapoport's rule has been quite variable (Gaston et al, 1998;Pintor et al, 2015;Tomašových et al, 2016): both findings for (Rohde et al, 1993) and against (Rohde, 1992) the existence of the rule have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, species with smaller range sizes have higher extinction risk (Payne & Finnegan, 2007) and are likely to have lower ability to track current and future climate change (Sunday et al, 2015). However, the mechanisms underlying patterns of range size are still controversial, despite many studies on the geographical variation of range size (Gaston, 2003;Pintor, Schwarzkopf, & Krockenberger, 2015). However, the mechanisms underlying patterns of range size are still controversial, despite many studies on the geographical variation of range size (Gaston, 2003;Pintor, Schwarzkopf, & Krockenberger, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of achieving smaller size at maturity at higher temperature through phenotypic plasticity in ectotherms is known as the temperature-size rule (Atkinson, 1994), while the same pattern at a larger geographic scale through genetic adaptation was termed Bergmann's rule (Bergmann, 1847), now extended from its original focus on vertebrates to all organisms (Blanckenhorn & Demont, 2004). Several other rules describing a similar pattern from different points of view were proposed (Blackburn et al, 1999;McNab, 2010;Alho et al, 2011;Pintor et al, 2015), but the most important is that despite these different points of view, the observation of growing larger at colder temperatures is so common in nature.…”
Section: Introductionmentioning
confidence: 99%